2015
DOI: 10.1038/srep07975
|View full text |Cite
|
Sign up to set email alerts
|

3D-DIP-Chip: a microarray-based method to measure genomic DNA damage

Abstract: Genotoxins cause DNA damage, which can result in genomic instability. The genetic changes induced have far-reaching consequences, often leading to diseases such as cancer. A wide range of genotoxins exists, including radiations and chemicals found naturally in the environment, and in man-made forms created by human activity across a variety of industries. Genomic technologies offer the possibility of unravelling the mechanisms of genotoxicity, including the repair of genetic damage, enhancing our ability to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…CPD formation is dictated mostly by sequence, and previous reports of the genome-wide distributions of this type of damage showed a relatively widespread signal that does not follow the enrichment patterns we observed (27,28). Furthermore, if higher initial repair were solely explained by higher levels of damage, we would expect similar enrichments in all time points.…”
Section: Regions Repaired Later Are Associated With Higher Mutagenesismentioning
confidence: 51%
“…CPD formation is dictated mostly by sequence, and previous reports of the genome-wide distributions of this type of damage showed a relatively widespread signal that does not follow the enrichment patterns we observed (27,28). Furthermore, if higher initial repair were solely explained by higher levels of damage, we would expect similar enrichments in all time points.…”
Section: Regions Repaired Later Are Associated With Higher Mutagenesismentioning
confidence: 51%
“…S8). Such a nucleosome photo-footprint was identified in mammalian chromatin nearly 30 y ago (11), but had been missed by previous genome-wide studies of CPD-formation (15,16,18,25). Nucleosomal DNA with an inward rotational setting is likely protected from UV damage as a result of constraints on DNA bending and flexibility imposed by the nucleosome structure (22).…”
Section: Discussionmentioning
confidence: 99%
“…8); however, past biochemical and cellular studies have suggested that nucleosomes and DNA-binding proteins may significantly alter the formation of UV damage (11)(12)(13)(14). Previous attempts to measure initial CPD levels using microarray-based methods (15)(16)(17) suggested that UV damage formation is primarily influenced by the DNA sequence. For example, CPDs occur most frequently at TT dipyrimidines, followed by TC, CT, and CC.…”
mentioning
confidence: 99%
“…To tackle this issue, we developed a genome-wide DNA repair assay based on ChIP-chip, referred to as 3D-DIP-Chip Powell et al 2015). The method permits the calculation of the relative repair rates at individual sites throughout the genome.…”
mentioning
confidence: 99%